Acute myelitis of children with positive anti-GM1 antibody: Case series and literature review. Issue 20 (May 2018) - Wang, Zhiling; Qie, Di; Zhou, Hui; Cai, Xiao tang
Abstract: Rationale: To explore the clinical features, treatment, and prognosis of acute myelitis (AM) of children with positive blood anti- ganglioside (GM1) antibodies. Patient concerns: Two cases of AM of children with positive anti-GM1 antibody were retrospectively collected and followed up for 6 months. Two cases had positive helicobacter pylori IgG antibody, and Case 2 also had positive mycoplasma IgM antibody. Diagnoses: Two cases had typical symptoms of myelitis, abnormal spinal magnetic resonance imaging (MRI), and positive serum anti-GM1 IgM. Interventions: They were treated with steroid, immunoglobulin and rehabilitation. Outcomes: Symptoms of AM were relieved after treatment. After 6 months of follow-up, case 1 was fully recovered and case 2 was partially recovered. Summarizing previous reports in literature and our 2 cases, AM with positive anti-GM1 antibody can be induced by multiple pathogen infections. About 35.7% were fully recovered, 42.9% had mild sequelae, and 21.4% had severe sequelae. Lessons: Post-infection immune injury plays an important role in the pathogenesis of AM with positive anti-GM1 antibody. H pylori and Mycoplasma pneumoniae infection may also induce AM with positive anti-GM1 antibody. Screening and treatment of pathogens were required and only 21.4% patients had severe sequelae after treatment.